DESIGN AND IMPLEMENTATION OF A WEB-BASED CAMPUS FACILITY BORROWING SYSTEM USING THE SIMPLE ADDITIVE WEIGHTING (SAW) METHOD (CASE STUDY: POLITEKNIK SUKABUMI) - Alghifari, Algi (SEMNASTERA (Seminar Nasional Teknologi dan Riset Terapan), 2025)
The development of information technology has encouraged educational institutions to adopt digital systems to improve efficiency and service effectiveness, including in managing campus facility reservations. The manual process of facility borrowing often causes schedule conflicts, delays, and a lack of transparency. To address these issues, this study aims to develop a web-based campus facility loan application capable of determining borrower priority objectively using the Simple Additive Weighting (SAW) method, and to evaluate the accuracy and effectiveness of the method in providing loan approval recommendations.The SAW method is applied as the decision-making basis by considering four criteria: activity impact, urgency, loan duration, and borrower status. Each criterion is weighted and normalized to produce a final score that determines the priority order of loan requests. The application was developed using the Laravel framework and MySQL database, with a web-based interface designed to simplify the borrowing and approval process for users and administrators.Based on testing results comparing the system output with manual Excel calculations, the system achieved an accuracy rate of 100%, indicating that the implementation of the SAW method works correctly and consistently with theoretical principles. Thus, the system can provide objective facility loan recommendations and improve decision-making efficiency within the campus environment.